La nutrición y el desarrollo motriz en niños de 3 a 6 años de la Unidad Educativa Puyango. Periodo 2023-2024 - Jiménez Requelme, Sandra Pahola (2024)
The present study aims to analyze the relationship between nutrition and motor development in children aged 3 to 6 years from the Puyango Educational Unit. Through a descriptive, analytical, and scientific methodology, it was investigated how nutrition impacts motor skills during this crucial stage of child growth. The results revealed that all parents provide their children with nutritious foods that enhance their motor development. This suggests a widespread awareness of the importance of healthy eating for the comprehensive development of children in that educational institution. The connection between nutrition and motor development in children aged 3 to 6 years is fundamental for their growth and well-being. The findings of this study reinforce the significance of a balanced diet rich in nutrients to enhance their physical abilities at the Puyango Educational Unit. It is imperative to continue promoting healthy eating habits in the school and family environment to ensure optimal motor development in children during this critical stage of their lives. Keywords: Nutrition, motor skills, comprehensive development